2019
DOI: 10.1055/s-0039-3400976
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Phenotypic Spectrum of Cerebral Aspartate–Glutamate Carrier Isoform 1 (AGC1) Deficiency

Abstract: Case We are reporting the third unrelated case of cerebral aspartate–glutamate carrier isoform 1 (AGC1) deficiency. Patient is a 21-month-old Yemeni male who presented with refractory seizure disorder and developmental arrest. Neuroimaging showed cerebral volume loss and diminished N-acetylaspartate (NAA) peak. Whole exome sequencing revealed a homozygous novel missense variant in the SLC25A12 gene. Patient's seizure frequency abated drastically following initiation of ketogenic diet. Discussion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 10 publications
(11 reference statements)
1
39
0
Order By: Relevance
“…Two other patients, two siblings with the homozygous mutation p.Arg252Gln (found in the SMS at position 34, Figures 1 and 2A,C, outside the pore) exhibited similar symptoms as the previous one; and the activity of the mutated protein was dramatically reduced but not completely abolished [91]. Recently, another disease-causing mutation, p.Thr444Ile ( Figure 2B,D, at position 130), has been found in the substrate translocation pore (Table S1), but the transport activity of this AGC1 variant has not been investigated [95].…”
Section: Slc25a12 (Aspartate-glutamate Carrier 1 Agc1 Aralar) Deficsupporting
confidence: 64%
“…Two other patients, two siblings with the homozygous mutation p.Arg252Gln (found in the SMS at position 34, Figures 1 and 2A,C, outside the pore) exhibited similar symptoms as the previous one; and the activity of the mutated protein was dramatically reduced but not completely abolished [91]. Recently, another disease-causing mutation, p.Thr444Ile ( Figure 2B,D, at position 130), has been found in the substrate translocation pore (Table S1), but the transport activity of this AGC1 variant has not been investigated [95].…”
Section: Slc25a12 (Aspartate-glutamate Carrier 1 Agc1 Aralar) Deficsupporting
confidence: 64%
“…Accumulating evidence also supports a pathogenic role of NAA deficiency in epilepsy. Severely reduced NAA was reported in patients with homozygous aspartate-glutamate carrier 1 (AGC1) mutations, which cause infantile epilepsy [ 65 , 66 , 67 , 68 ]. Based on the fact that AGC1 mediates the efflux of aspartate from neuronal mitochondria to cytoplasm, it has been proposed that the deficient function of AGC1 leads to impaired transportation of aspartate to the cytoplasm, where can be metabolized to NAA [ 69 ].…”
Section: Potential Impacts Of Decreased Brain N-acetylaspartate Anmentioning
confidence: 99%
“…Hence, the decreased aspartate in MSUD may affect oxidative phosphorylation and adenosine triphosphate production in neurons (reviewed elsewhere [ 15 ]). Furthermore, studies reported that MAS deficits are associated with infantile-onset epileptic encephalopathies [ 65 , 66 , 67 , 68 , 77 , 78 ] and autism [ 79 , 80 , 81 , 82 ]. In short, reduced aspartate levels in the CNS of MSUD patients may decrease MAS flux and contribute to neurologic symptoms in MSUD patients.…”
Section: Potential Impacts Of Decreased Brain N-acetylaspartate Anmentioning
confidence: 99%
“…KD has been proved to be beneficial in patients with pharmaco-resistant epilepsy (Klepper et al, 2007;Kossoff et al, 2009;Villeneuve et al, 2009;Kessler et al, 2011) and, interestingly, in several metabolic disorders like GLUT-1 deficiency (Alter et al, 2015) and MPC-1 deficiency (Vanderperre et al, 2016). Indeed, it has also been proposed as a therapeutic diet in several neurologic diseases as Alzheimer's disease (Van der Auwera et al, 2005), amyotrophic lateral sclerosis (Zhao et al, 2006), Huntington's disease (Ruskin et al, 2011), autism (Ruskin et al, 2013), Parkinson's disease (VanItallie et al, 2005), and as previously mentioned in two patients with Aralar/AGC1 deficiency (Dahlin et al, 2015;Pfeiffer et al, 2020).…”
Section: Introductionmentioning
confidence: 90%
“…In humans, Aralar/AGC1 deficiency causes the rare disease "global cerebral hypomyelination" (OMIM #612949, also named early infantile epileptic encephalopathy 39), a neurodevelopmental disease that matches aralar-KO mice phenotype, as it is characterized by severe hypomyelination, hypotonia, neurodevelopmental arrest, and seizures (Wibom et al, 2009;Falk et al, 2014;Kavanaugh et al, 2019;Pfeiffer et al, 2020). The first patient described for Aralar/AGC1 deficiency initiated a treatment with ketogenic diet (KD) at the age of 6 and for at least 19 months.…”
Section: Introductionmentioning
confidence: 99%